Analisis Perbandingan Google Home Dan Amazon Alexa Pada Rumah Pintar (Smart Home) - Gera Nugraha; Fernando Juliansyah; Farhan Firdaus; Didik Aribowo (Jurnal Sains dan Teknologi, 2023)
This analysis will help Smart Home users to understand the advantages, disadvantages, and significant differences between these two platforms. With this more in-depth information, users will be able to make smarter decisions in choosing the platform that best suits their needs and preferences in managing their Smart Home.